2013
DOI: 10.12938/bmfh.32.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diet on Gut Microbiota Profile and the Implications for Health and Disease

Abstract: Gut microbes are present in large concentrations on the human intestinal mucosal surface and play important roles in health and disease of the host. Numerous groups of gut microbes are associated with immunological and metabolic diseases and in maintaining health status of the host. Among these health- and disease-associated gut microbes, Bacteroides, Clostridium and Bifidobacterium appear regularly in the list. Scientific and clinical evidence available to date indicates that diet is a major driving factor fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 131 publications
(126 reference statements)
0
33
0
1
Order By: Relevance
“…Detailed Clostridium species information was not fully elucidated by our analysis and further studies are warranted to investigate the effects of a BRB diet or individual components on Clostridium species and their potential health effects. Polyphenols from red wine and tannin‐rich diets have been reported to significantly decrease the growth of Clostridium species while stimulating Lactobacillus and Bifodobacterium . Dueñas et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed Clostridium species information was not fully elucidated by our analysis and further studies are warranted to investigate the effects of a BRB diet or individual components on Clostridium species and their potential health effects. Polyphenols from red wine and tannin‐rich diets have been reported to significantly decrease the growth of Clostridium species while stimulating Lactobacillus and Bifodobacterium . Dueñas et al.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols from red wine and tanninrich diets have been reported to significantly decrease the growth of Clostridium species while stimulating Lactobacillus and Bifodobacterium. [63][64][65] Dueñas et al reviewed studies on the modulation of gut microbiota by dietary polyphenols according to experimental design. [66] Food polyphenols or their extracts have been shown to increase Lactobacillus and Bifodobacteria in the majority of the animal and human intervention studies, yet some observed decreases or no change.…”
Section: Impact Of Brb Intervention On Gut Microbial Communitymentioning
confidence: 99%
“…Environmental factors, including geographical region, family size and exposure to pets, are thought to shape the gut microbiota of early life . For example, in young children from China, Japan and Taiwan, Bifidobacterium and Bacteroides are the most common bacterial clusters, whereas Prevotella is more predominant in children from Indonesia and Thailand .…”
Section: Resultsmentioning
confidence: 99%
“…Environmental factors, including geographical region, family size and exposure to pets, are thought to shape the gut microbiota of early life. 28,38,39 For example, in young children from China, Japan and Taiwan, Bifidobacterium and Bacteroides are the most common bacterial clusters, whereas Prevotella is more predominant in children from Indonesia and Thailand. 40 In addition, infants with older siblings have higher counts of Bifidobacteriaceae and lower counts of Peptostreptococcaceae, compared with infants without older siblings.…”
Section: Statement 6: Antibiotic Exposure During Pregnancy and Infancmentioning
confidence: 99%
“…shows that there is a mutual relationship between the intestinal microbiota and its host, which is believed to be crucial determinant of health and disease. The host provides their intestinal bacteria a protected nutrient-rich environment, while the bacteria make essential contributions for polysaccharide digestion [48], defense against infections and synthesis of vitamins [24]. Studies using germ-free animals show that the acquisition of symbiotic microbes is critical for the normal function of the intestine [49,50].…”
Section: Figure 2b and 2cmentioning
confidence: 99%